Indocyanine green imaging for pulmonary segmentectomyCentral MessagePerspective - Masaya Yotsukura, MD; Yu Okubo, MD; Yukihiro Yoshida, MD; Kazuo Nakagawa, MD; Shun-ichi Watanabe, MD (JTCVS Techniques)
Objective: Delineation of the intersegmental plane during pulmonary segmentectomy by systemic injection of indocyanine green (ICG) has been rapidly emerging. We evaluated the feasibility of the use of ICG in a large-scale cohort according to the type of segmentectomy and the presence of obstructive lung disorder and compared the demarcation status with air injection. Methods: We collected the data of 209 patients who underwent segmentectomy using ICG at National Cancer Center Hospital, Tokyo, Japan. Data of the operation including the demarcation status of the intersegmental plane were analyzed retrospectively. Results: The median operation duration and blood loss were 105 minutes (interquartile range, 94-118 minutes) and 12 mL (interquartile range, 5-24 mL), respectively. Good demarcation of the intersegmental plane by ICG was observed in 184 (88.0%) cases, with no correlation to the type of resected segments or the presence of obstructive lung disorder. Postoperative complications of Clavien–Dindo classification grade 3 or more were observed in 5 cases (2.4%), and no ICG-related adverse event was noted. High-frequency jet ventilation was also used in 160 cases (76.6%) to delineate the intersegmental inflation–deflation plane. The air injected by high-frequency jet ventilation tended to spread further beyond the intersegmental plane that was depicted by ICG. Conclusions: The use of ICG might demarcate the intersegmental plane more restricted to the target segment compared with air injection. Delineation of the intersegmental plane by ICG is feasible regardless of the type of segmentectomy or the presence of obstructive lung disorder, and it can be commonly applicable in pulmonary segmentectomy.